The Cambridge companion to Leibniz - Jolley, Nicholas (Cambridge [u.a.] Cambridge Univ. Press, 1995)
The most comprehensive account of the full range of Leibniz's thought
G.W. Leibniz, life and works / Roger Ariew -- The seventeenth-century intellectual background / Stuart Brown -- Metaphysics : the early period to the Discourse on metaphysics / Christia Mercer and R.C. Sleigh, Jr. -- Metaphysics : the late period / Donald Rutherford -- The theory of knowledge / Robert McRae -- Philosophy and logic / G.H.R. Parkinson -- Philosophy and language in Leibniz / Donald Rutherford -- Leibniz : physics and philosophy / Daniel Garber -- Leibniz's ontological and cosmological arguments ; Perfection and happiness in the best possible world / David Blumenfeld -- Leibniz's moral philosophy / Gregory Brown -- The reception of Leibniz in the eighteenth century / Catherine Wilson
The reception of Leibniz in the eighteenth century Catherine Wilson.
Hier auch später erschienene, unveränderte Nachdrucke
Literaturverz. S. 475 - 493
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Leibniz, Gottfried Wilhelm -- Freiherr von -- 1646-1716; Bibliografie; Aufsatzsammlung; Einführung